2004
DOI: 10.1177/10483713040180010106
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Music Centers in the Early Childhood Class

Abstract: I n 1960, Jerome Bruner, a psychologist at Harvard University, wrote a small book called The Process of Education, in which he challenged educators to rethink what and how they were teaching. He stated his belief that "Any subject can be taught effectively in some intellectually honest form to any child at any stage of development" if the teaching represents "the structure of the subject" and is presented "in terms of the child's way of viewing things" (p. 33). Bruner was suggesting that to be effective, teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Principally, we design sets of materials related to listening and singing and which foster activities focused on music experimentation. In line with Kenney (2004), we believe that children learn by interacting with their environment and therefore opted for materials as one pathway for providing such an environment. Each material is used as a basis for a specific activity (Malagarriga & Pérez, 2008) while simultaneously serving as the starting point to facilitate further ones.…”
Section: Materials For Music Makingmentioning
confidence: 83%
“…Principally, we design sets of materials related to listening and singing and which foster activities focused on music experimentation. In line with Kenney (2004), we believe that children learn by interacting with their environment and therefore opted for materials as one pathway for providing such an environment. Each material is used as a basis for a specific activity (Malagarriga & Pérez, 2008) while simultaneously serving as the starting point to facilitate further ones.…”
Section: Materials For Music Makingmentioning
confidence: 83%
“…Music educators can foster music growth through creating an environment supportive of music play and incorporating more free or open-ended play in the music classroom (Berger & Cooper, 2003;Dansereau, 2011;de Vries, 2006;Hornbach, 2011;Smith 2008;Yanko, 2015). For instance, music teachers can develop a music play-supportive classroom environment with the use of centers (Berger & Cooper, 2003;Kenney, 2004). Bond (2013) recommended music teachers guide and support children's music play with Reggio Emiliainspired documentation to make learning visible.…”
Section: Play and Music Educationmentioning
confidence: 99%
“…In addition to the general play that children participate in, researchers' observations of children have concluded that children sing, dance, and improvise on their own and that children will take part in all music-making practices if they are allowed to do so and as they feel ready (Kenney, 2004). As researchers have continued to study early childhood music, data have revealed that musical play was crucial in the development of a child's musical capabilities.…”
Section: Musical Playmentioning
confidence: 99%